2014
DOI: 10.1016/j.jare.2013.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Risk assessment of desert pollution on composite high voltage insulators

Abstract: Transmission lines located in the desert are subjected to desert climate, one of whose features is sandstorms. With long accumulation of sand and with the advent of moisture from rain, ambient humidity and dew, a conductive layer forms and the subsequent leakage current may lead to surface discharge, which may shorten the insulator life or lead to flashover thus interrupting the power supply. Strategically erected power lines in the Egyptian Sinai desert are typically subject to such a risk, where sandstorms a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 5 publications
1
17
0
Order By: Relevance
“…Figure 10 shows the electric field distribution in string with 10 unit of insulator. It is observed that the present of the broken shed in the insulator has decreased the average electric field distribution in string; this findings is agreed by Shahat [18]. Figure 11 shows the electric field distribution of 10 units of porcelain insulator in a string.…”
Section: Electric Field Distribution Across a Porcelain Insulator Stringsupporting
confidence: 71%
“…Figure 10 shows the electric field distribution in string with 10 unit of insulator. It is observed that the present of the broken shed in the insulator has decreased the average electric field distribution in string; this findings is agreed by Shahat [18]. Figure 11 shows the electric field distribution of 10 units of porcelain insulator in a string.…”
Section: Electric Field Distribution Across a Porcelain Insulator Stringsupporting
confidence: 71%
“…Three parameters Weibull distribution function has been utilized for the statistical model of the flashover occurrence and can be represented as [36] (22) U 0 , U AV , U C , R hio , and R hi(av) are withstand voltage (probability flashover =0), average flashover voltage, continuous operating voltage. LC index value when flashover probability is zero and the average value of LC index obtained at each pollution level, k, α, and γ are constant and n is the constant equal to 2 [35].…”
Section: B Flashover Occurrence Probability Based On Lc Indexmentioning
confidence: 99%
“…Failures in high voltage insulators is frequently initiated with the leakage current flow [39], and this important factor is considered in this investigation. Figure 16 shows the leakage conduction current density distribution along the insulator profile for Scenarios 1 to 4.…”
Section: Conduction Current Densitymentioning
confidence: 99%